Marketing Strategy for Financing Products of PT. Bank of North Sumatra KCP Syari'ah Simpang Kayu Besar - Aini Rahma; Muhammad Latief Ilhamy Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Each Islamic bank has a variety of products offered according to the needs of the community. In offering their products, there is competition between Islamic banks and conventional banks, so there needs to be a strategy in marketing each of these banks. Marketing is often identified with a world full of sweet promises but it is not necessarily proven whether the product is in accordance with what has been promised. This is what must be proven in a sharia marketing management both in the sale of goods or services, that sharia marketing is not a world full of deceit. Because sharia marketing is the highest tingkat in marketing, namely kebatinan marketing, where ethics, values and norms are upheld. This research is motivated by the development of Islamic banks which positively contribute to economic stability, but in practice there are still criticisms. Likewise, Mukmin scholars and scholars have different opinions about the position and position of Islamic banks, some of them think that Islamic banks are the same as conventional banks. The results showed that the implementation of the marketing of financing products at PT. Bank Sumut Kcp Syariah Simpang Kayu Besar.